Students’ Ability in Conversation (The Case of SMPN 3 Teminabuan Grade IX) - Ida Siti Hamidah; Melinda Roza; Lidwina Sri Ardiasih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to know the students’ ability level, students’ problems, and solution in conversation. Researcher describes the same conditions that have occurred in the Teminabuan district, West Papua. In this area, students experienced difficulties in learning English, especially in communication or conversation. Researcher used qualitative research methods, because they fit perfectly with the problem under study. The research instruments were observation, data of documentation, and interviews with students and English teachers at SMPN 3 Teminabuan. Research data in this study used documentation, observation and interview that was asked and questioned to respondents to be done and answered in order to get valid answers. In addition, researcher also monitors students learning methods and learning systems to measure students’ abilities in learning English conversation. The documentation that used were 20 dialogs of conversation and the interview were questions that had been provided. Data Analysis obtained by means of qualitative descriptive techniques in the form of descriptions of phenomena that occur in the SMPN 3 Teminabuan district. The results show that the factors that influence the level of students' ability in English conversation are lack of mastery of five basic elements, namely fluency, grammar, vocabulary, pronunciation and comprehension.